Osilodrostat therapy in a 26-year-old patient after ineffective surgical treatment of Cushing Disease: a case report - Kamińska, Magdalena; Strzoda, Adam; Juda, Agata; Rojek, Kornelia; Strzoda, Anna; Sowiński, Wojciech; Polak, Agnieszka (Journal of Education, Health and Sport, 2022)
Cushing’s Disease is caused by pituitary adenoma which produces adrenocorticotropic hormone causing hypercortisolemia. First-line treatment involves operative removal of the tumor, however, in some patients it proves ineffective. In those cases, pharmacological treatment is necessary as untreated Cushing’s Disease may be lethal. In 2020 a new steroidogenesis inhibitor – Osilodrostat - was approved by the European Medicines Agency and can be used in the treatment of patients who cannot undergo pituitary surgery or whose previous surgical treatment proved ineffective. We present a case of a 26-year-old female patient who was diagnosed with endogenous Cushing’s Disease and underwent two consecutive operations to remove the tumor - both were ineffective. With deteriorating laboratory results and other pharmacological treatments exhausted Osilodrostat therapy was introduced. Osilodrostat is becoming an important drug in patients with Cushing’s Disease refractory to other treatments.